The potential of technology assisted engineering problem solving tool for engineering education - Lee C.K.; Sidhu M.S. (American Scientific Publishers, 2023)
In knowledge based society, interactive multimedia has become one of the most attractive and promising technologies in education. For engineering education, one of the common problems faced by the students is the difficulty in visualizing some of the engineering concepts that involved dynamic motions, complex calculations particularly in z-axis. The problems posed to these students usually need to be solved by using appropriate formulas and may lead to a series of working steps before gaining the solution. This research focused on the design and development of a 3D simulation engineering problem solving tool to facilitate the learning and problem solving in engineering. Initial preliminary results showed that positive outcome was obtained through the study. The interactive simulated engineering problem solving tool could assist the Mechanical Engineering students by enhancing their learning interest and improved the visualization ability in the engineering mechanics dynamics domain. 2016 American Scientific Publishers. All rights reserved.